UPAYA PENGHEMATAN ENERGI PENYEJUK BANGUNAN MELALUI MODIFIKASI DESAIN FASAD PADA TOWER HOTEL @HOM SEMARANG - Patricia Mayasari Krisnawan; Paulus Agus Susanto (Riset Arsitektur (RISA), 2022)
Abstract - Hotel @HOM Semarang is one of several high-rise buildings in the central area of ​​Semarang City. During the several years the building has been operating, there have been several problems encountered by the hotel, such as the penetration of solar heat in hotel rooms facing the Northwest and Southeast directions. Preliminary research results at the Hotel @HOM Semarang indicate that the overall thermal transfer value or OTTV of the building still exceeds the recommended value. This study aims to determine alternative facade modifications that can be applied to Hotel @HOM as an effort to save energy in building conditioning and determine the potential uses of alternative facade modifications for Hotel @HOM. The research uses quantitative methods with a case study approach. Energy evaluation was carried out by manual calculation using a Microsoft Excel spreadsheet based on the thermal balance and OTTV methods. Efforts to reduce cooling energy consumption were chosen based on consideration of minimal structural changes. The modifications made consisted of adding external shade which was divided into second skin and shade fins, window-to-wall ratio reduction, changing the glass material on the windows, and changing the paint color of the outer walls. The existing building and the modifications made are then calculated to determine the cooling energy savings produced and compared to determine the peringkat. Based on the calculation results, the modification with the highest saving effectiveness is through the addition of a second skin, followed by window-to-wall ratio reduction, changing the glass material, adding shade fins, and changing the paint color of the outer walls. The modification with the highest cost savings is the addition of shade fins, followed by changing the paint color of the outer walls, adding a second skin, changing the glass material, and window-to-wall ratio reduction. Based on the opinions of practitioners in the fields of architecture, construction, and building management which were collected through questionnaires and analyzed using the RII (Relative Important Index), the modification with the highest rank was the addition of shade fins, followed by the addition of a second skin, window-to-wall ratio reduction, replacing glass material, and changing the paint color of the outer walls. Keywords: Energy saving, Cooling load, Façade, Semarang